Pelaksanaan Mediasi Elektronik Di Pengadilan Dalam Tinjauan Hukum Acara Perdata - Hanafiah, Zahira Nurmahdi (INDO PUBLISHING, 2025)
The purpose of this study is to analyze the application of electronic mediation in court in the context of civil procedural law. The development of the digital era has brought changes in various fields, including the justice system. One form of adaptation is the emergence of electronic mediation in the courtroom. Regulation of the Supreme Court of the Republic of Indonesia No. 3 (2022) regulates electronic mediation in court (Perm No. 3/2022), providing an alternative means of dispute resolution that is more practical, efficient and easily accessible. This study comprehensively analyzes the application of electronic mediation in court from the perspective of civil procedural law. The study begins with a discussion of regulations regarding electronic mediation in court, such as Perma Number 1 of 2016 and Perma Number 3 of 2022. The analysis then focuses on the benefits, challenges, and implications of the application of electronic mediation in civil procedural law. This article also assesses the opinions of legal experts on the importance of integrating e-mediation into a comprehensive online justice system as well as education and training for all parties and mediators. The use of electronic mediation in court creates opportunities and challenges from a civil procedural law perspective. It is hoped that with the cooperation of various stakeholders, e-mediation will be an effective and fair solution in resolving disputes in Indonesia.